Selected poems of Garcilaso de la Vega: a bilingual edition - Vega, Garcilaso de la (The Univ. of Chicago Press, 2009)
Sonnets. Introduction -- I cuando me paro a contemplar mi estado = When i stop to view my situation . . . -- Escrito está en mi alma vuestro gesto = Your countenance is written in my soul . . . -- [MARC+96]Oh dulces prendas, por mi mal halladas = O sweet mementoes, unfortunately found . . . -- Hermosas ninfas, que en el río metidas = Slender nymphs who dwell within the river . . . -- A Dafne ya los brazos le crecían = Daphne's arms were growing . . . Pensando que el camino iba derecho = Thinking that the road i took was straight . . . -- En tanto que de rosa y azucena = While colors of the lily and the rose . . . -- [MARC+96]Oh hado esecutivo en mis dolores = O fate, so active to promote my troubles . . . -- Sospechas, que en mi triste fantasía = Suspicion, how you occupy my sad . . . -- Estoy contino en lágrimas bañado = I am continually half drowned in tears . . . -- Mario, el ingrato amor, como testigo = Mario, love the ingrate having observed . . . -- Boscán, las armas y el furor de marte = Arms, boscán, and the fury of rampant Mars . . . -- Mi lengua va por do el dolor la guía = My tongue simply follows where pain leads . . . -- Songs. Introduction -- Con un manso ruido = With the gentle lapping . . . -- Si de mi baja lira = If the sound of my simple . . . -- Elegies and epistle to Boscan. Introduction -- I aunque este grave caso haya tocado = Although this dread event has touched my soul . . . -- Aquí, Boscán, donde del buen troyano = Here, Boscán, where the great Mantuan locates . . . -- Epistle señor Boscán, quien tanto gusto tiene = Señor Boscán, for one who takes such pleasure . . . -- Eclogues. Introduction -- I el dulce lamenter de dos pastores = Of two shepherds' melodious laments . . . -- From ii en medio del invierno está templada = Even in the depths of winter, the water . . . -- Aquella voluntad honesta y pura = That pure and honorable sense of duty . . . -- Appendix A: two coplas -- Appendix B: letter (as a prologue to Boscán's translation of Castiglione's The book of the courtier)